Opini Publik tentang Destinasi Pariwisata Danau Toba sebagai Global Geopark Kaldera UNESCO melalui Website Kompas.Com - Muhammad Yusuf Fahrizal; Yan Hendra; Taufik Wal Hidayat (Universitas Medan Area, 2020)
This research is motivated by the existence of public opinion about the issue of discourse of Lake Toba tourism destination as a global Toba Caldera Geopark by UNESCO which was pioneered by the Central and Regional Government through the website kompas.com. the problem in this study is how Student / Student opinion about the issue of discourse of Lake Toba tourism destinations as a global UNESCO Geopark Caldera. The research objective was to find out public opinion about Danau Toba tourism as a global UNESCO Geopark Caldera. To obtain this data used descriptive quantitative research method with analysis of respondents' distribution tables. The research technique was carried out by distributing questionnaire to 60 respondents who were active students of USU's Communication Department. The results of the study that public opinion is combined with the research conceptual framework, namely the AIDDA theory consists of attention, interest, desire, decision, action to produce public opinion on the issue of Lake Toba tourism destination discourse as global UNESCO Geopark Caldera.